PHONOLOGICAL DIALECT DIFFERENCES OF KARONESE LANGUAGE IN MEDAN, NORTH SUMATRA - Sesilia Br Gurusinga (Jurnal CULTURE (Culture, Language, and Literature Review), 2020)
In this research, the writer analyzes about Phonological dialect differences of Karonese Language, in which it is studied in dialectology. Dialectology is a study of geographical varieties of language. Whereas, dialect is the language of a group of people living in a particular area. The data that are used from primary and secondary sources. The method of data collections are observation method, interview method and introspective method. To analyze the data, the writer used equalizing method and distributional. The method of data presentation used formal method and informal method. In karo language there are 6 vowels, 15 consonants, 18 diphthong and 7 triphtongs. In karo language, there vowel variation such as vowels /i/ and /ɪ/, /a/ and /æ/, /ʊ/ and /ᴐ/, /ʊ/ and /ǝ/, /ǝ:/ and /i:/. There are also vowel variations to be diphthong variations like; /e/ to be /ai/, /o/ to be /au/. In karo language was found diphthong variation to be triphtong variations, such as; /oi/ to be /aui/, /io/ to be /iau/, /ue/ to be /uai/ and /uei/, /ie/ to be /iai/ and /iei/. In karo language there are some vowels that is pronounced but it is not written, like; /a: /æ/, /i:/, /ɪ/ /e:/, /ǝ:/, /ᴐ/.